It tastes sweeter when melted: Exploring the impact of food temperature on tongue temperature and perceived sweetness/vanilla - Hannah McNeill; Rebecca Ford; Ian Fisk; Margaret Thibodeau; Gloria Liu; Marion Doyennette; Qian Yang (Science Talks)
The relationship between perceived sweetness intensity and temperature of food is complex. Previous research on the effect of temperature on sweetness perception primarily focused on single solutions. This study aimed to address the gap by using an infrared camera to measure tongue surface temperature, explore tongue temperature ranges, the relationship between sweet/flavour and tongue temperature at different serving temperatures during real food consumption. Participants (n = 22) consumed custard served at warm (59.1 ± 0.8 °C), ambient (24 ± 0.6 °C), chilled (4.6 ± 0.5 °C), and frozen (−2.7 ± 0.3) temperatures. An infrared camera was used to capture participant tongue surface temperature. Sweetness and vanilla intensity were recorded using a modified General Labelled Magnitude Scale. This study demonstrated that infrared imaging could effectively capture tongue surface temperature. Results revealed tongue surface temperature recovered to baseline more efficiently after cooling than warming. A weak positive correlation was found between tongue surface temperature, perceived sweetness (r = 0.234, p-value = 0.002) and vanilla intensity (r = 0.226, p-value = 0.003). Perceived sweetness intensity was significantly higher for warm custard (tongue = 37.3 °C, sweetness = 20.5) than frozen custard (tongue = 27.1 °C, sweetness = 13.3). This suggests that temperature changes on the tongue during food consumption could significantly contribute to the perceived intensity of sweetness. The findings provide valuable insights to food industries interested in sugar reduction.